Caracterización del Sistema de Tenencia, Perfil Hematológico y Bioquímico del Cerdo Criollo Ecuatoriano en la Provincia de Cotopaxi. - Moreta Cevallos, Verónica Carolina (2019)
This research was carried out in 3 cantons of Cotopaxi (La Mana, Pangua and Sigchos), with the objective of characterizing the tenure system and establishing the Hematological - Biochemical profile in the Ecuadorian Creole pig. The tenure system was characterized through 30 surveys that were carried out to the animals owners, seeking to collect general data, human resources, exploitation data, reproductive data, productive data, feeding system and sanitary management. In the analysis of the surveys results were found that most of the people had a primary education so their responses were very punctual, allowing to know in productive, reproductive and health management lack the knowledge regarding the raising of the Creole pig. The hematological-biochemical profile study was carried out in 30 Creole pigs, from which blood samples were taken that were extracted from the atrial vein by puncture; the samples were analyzed in the "San Francisco" Clinical Laboratory located in Ambato. After having the results, the statistical values analysis of all the hematological profile variables (hematocrit, hemoglobin, erythrocytes, VGM, MCH, CGMH, platelets, leukocytes, neutrophils, n. Bands, lymphocytes, monocytes, eosinophils, basophils) and the biochemical profile (glucose, urea, BUN, creatinine, AST, ALT, total proteins, calcium, phosphorus, potassium) were done. For the haematological and biochemical profile the Fisher and Tukey test was performed for the leukogram in Infostad taking into account a confidence interval 0.5%, the sex effect was evaluated on the different variables where observed only significant difference in the variable Calcium where females have higher ranges than males. This is because the hematological and biochemical parameters vary with age, physiological status, race, sex, nutrition, climate, stress and production type.